Dampak Perkembangan Pariwisata Terhadap Kondisi Sosial Ekonomi Masyarakat Di Pulau Nusa Lembongan - Shantika, Budi; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2018)
This research was conducted based on the condition of the development of tourism on the island of Nusa Lembongan, aiming to find out the impact brought about by socio-economic conditions against the tourism society.This study uses qualitative and quantitative approach with mix method, the primary data source that are obtained by observations and direct interviews and secondary data. The sampling technique used was purposive sampling techniques and data analysis using the method of case study. This study shows tourism provides impact on society and the government on the island of Nusa Lembongan are seen from eight aspect among others : impact increasing of foreign exchange, impact toward local community income that increasing before tourism exist, impact toward higher prices than the real prices, impact toward employment for opportunity to local community, ownership and control of tourism accommodation, the distribution of benefits and advantage against indigenous village, development in general are seen from 4A tourism and government income of tax viewed from PHR. Advice can be given to government and businessman and tourism service on the island of Nusa Lembongan in the order of future improve the facilities, infrastructure supporting tourism, reinforce the rules on the division of the proceeds against the indigenous villages, improving access and employment for local community on the island of Nusa Lembongan.   Key Words              : Tourism, Nusa Lembongan Island, Impact